ANALYSIS OF THE EFFECT OF WIND CHARACTERISTICS AND PSBB REGULATION ON PM2.5 POLLUTANTS CONCENTRATION IN CENTRAL JAKARTA (CASE STUDY: MARCH - NOVEMBER 2020) - Sabila Waskitaningsih, Desiana
Concentration of pollutants can be affected by wind speed and number of vehicles. The implementation of the PSBB regulation which took place in Jakarta in 2020 during the Covid- 19 pandemic significantly reduced the number of vehicles passing through Central Jakarta. Although the concentration of PM2.5 is observed to continue to increase every year, in 2020 it has decreased significantly. Therefore, an analysis of wind characteristics and the effect of the PSBB policy is needed to determine the effect of these two factors on decreasing PM2.5 concentrations in 2020. In this study, daily PM2.5 concentration data, wind speed and direction data from 2017 to 2020, and the number of daily vehicles for the MAM, JJA, and SON periods in 2020. The data is then processed to see correlation values, seasonal patterns, and the relation between both variables on the concentration of PM2.5. The results showed that PM2.5 concentrations tended to be high in the JJA period and low in the MAM period. PM2.5 concentration in Central Jakarta in March-November 2020 is more influenced by the number of vehicles than wind speed. Based on the results of the visualization of the estimated distribution of PM2.5, it shows that PM2.5 in MAM has the potential to spread to the west, when JJA is to the east, and when SON is to the west.